Christa Comes Out of Her Shell : a novel - Waxman, Abbi (New York : Berkley, 2024)
"After a tumultuous childhood, Christa Liddle has hidden away, both figuratively and literally. Happily studying sea snails in the middle of the Indian Ocean, Christa finds her tranquil existence thrown into chaos when her once-famous father--long thoughtdead after a plane crash--turns out to be alive, well, and ready to make amends. The world goes wild, fascinated by this real-life saga, pinning Christa and her family under the spotlight. As if that weren't enough, her reunion with an old childhood friend reveals an intense physical attraction neither was expecting and both want to act on . . . if they can just keep a lid on it. When her father's story starts to develop cracks, Christa fears she will lose herself, her potential relationship, and--most importantly--any chance of making it back to her snails before they forget her completely."--.
"Readers guide included"--Page 4 of cover.
new book 2024 spring.
Keywords: Women scientists -- Fiction; Fathers and daughters -- Fiction; Dysfunctional families -- Fiction